Interactive effects of land‐use history, tree encroachment and distance to edge on species richness in an unmanaged heathland. Issue 1 (20th October 2016) - Kepfer‐Rojas, Sebastian; Damgaard, Christian; Riis‐Nielsen, Torben; Schmidt, Inger Kappel
Abstract: Questions: How do land‐use legacies, tree encroachment and distance to the edge interact to determine species richness patterns in the ground vegetation of an unmanaged heathland? What are the direct and indirect effects of these factors? Do different functional groups respond differently to these factors? Location: Nørholm heathland, southwest Denmark. Methods: We recorded the overstorey and ground vegetation along with environmental variables in 129 plots on a 350 ha heathland where management ceased more than 100 yrs ago. We used structural equation models (SEM) to examine the relationship between species richness of functional groups (herbs, dwarf shrubs and tree seedlings) and ground vegetation cover, overstorey development, distance to the edge and nutrient availability. Results: The relative importance of the driving factors differed between functional groups. Herb richness increased with increasing nutrient availability from previous land use and decreased with overstorey development. Dwarf shrub richness responded negatively to overstorey development and herb cover. In contrast, species richness of tree seedlings responded strongly and positively to overstorey development but not to environmental variables or ground vegetation. In general, the effect of nutrient availability and distance to the edge were of similar magnitude and were largely mediated by the overstorey and ground vegetation. Conclusions: Land‐use legacies and tree encroachment can have differential effects on the species richness of different functional groups. Typical heathland dwarf shrubs were able to withstand moderate levels of increased nutrient availability and tree colonization. However, the combination of these factors poses a serious threat, as dwarf shrub richness decreased due to an increase in the cover of herbaceous species and light limitation. The absence of management did not lead to a rapid loss of typical heathland species. Abstract : We used structural equation modeling to analyze how land use legacies, tree encroachment and colonization interact to determine species richness patterns of herbs, tree seedlings and dwarf shrubs in a heathland left without management ca. 120 yrs ago. We show how the effects of these factors depend on the functional groups. A possible plant‐soil feedback mechanism is also suggested.